Relationship between shoulder ultrasound findings and disease activity in patients with rheumatoid arthritis: A pilot study - Merve Akdeniz Leblebicier,; Fatıma Yaman,; İsmail Saraçoğlu,; Vural Kavuncu,; Meltem İmal Kızılkaya, (Archives of Rheumatology, 2022)
Objectives: The aim of this study was to investigate whether shoulder ultrasound (US) findings were associated with disease activity and pain level in rheumatoid arthritis (RA) patients. Patients and methods: Between April 2019 and November 2019, a total of 60 shoulders of 30 female patients with RA (mean age: 53.8±12.0 years; range, 30 to 65 years) were included. The patients were questioned about shoulder pain and their Disease Activity Score-28 (DAS28) was estimated. After clinical examination with shoulder impingement tests, both shoulders were evaluated by US. Results: Of 60 shoulders examined by shoulder US, the most common shoulder pathology was supraspinatus tendinopathy (n=33, 55%). The prevalence of subdeltoid bursitis on US was significantly higher in the group with moderate disease activity, compared to the group with low disease activity (p<0.05). There were no significant differences in the physical examination findings of patients with low and moderate disease activity. In terms of US findings, subscapularis tendinopathy, glenohumeral joint and acromioclavicular joint degeneration, and subacromial bursitis were more common in shoulders with a history of pain, compared to non-painful shoulders. Conclusion: Shoulder US may be useful for demonstrating shoulder involvement in patients with RA, independent of the presence of shoulder pain.